KERJASAMA INVESTASI AMERIKA-INDONESIA DALAM ENERGI BARU TERBARUKAN STUDI KASUS PROGRAM PEMBANGKIT LISTRIK TENAGA BAYU SIDRAP I PERIODE 2015-2018 - Tasya Yasinki (2020)
The lack of the NRE mix is seen from the dominant primary energy such as fossil energy in the current energy mix. By setting a target for the NRE mix in 2025 of 23% and a commitment to reduce greenhouse gas emissions for the world, the development and use of new renewable energy is needed by carrying out the construction of an NRE power plant. The efforts to realize the development, still have challenges in terms of funding, technology, and qualified human resources in the field of NRE. Therefore, conducting investment cooperation with other countries both with the private sector in the field of NRE will help Indonesia reduce challenges and provide opportunities to accelerate and improve the NRE mix. Through research under the title "US-Indonesia Investment Cooperation in Rew Renewable Energy Case Study of The Sidrap Wind Power Plant Program Phase 1 Period 2015-2018"with the formulation of the problem of how the implementation of investment cooperation in the construction of SIDRAP PLTB I. The purpose of this study is to determine the form and scheme of Investment cooperation namely Independent Power Producer (IPP), namely UPC Renewables, an American private company with PT. PLN (Persero) as an electric energy buyer representing Indonesia, this program is expected to help increase the EBT mix in Indonesia. The research approach used is qualitative by using Primary and Secondary data sources from related agencies, media or companies. This data was analyzed using the concept of New Renewable Energy, Foreign Direct Investment and implementation of the Policies that underlie the construction of the PLTB SIDRAP I Period 20152018.